Developing a methodology to evaluate climate services for farmers in Africa and South Asia workshop report - Tall, Arame; Njinga JL (2013)
This report summarizes the proceedings of the international expert roundtable on “Developing a Methodology to Evaluate Climate Services for Farmers in Africa and South Asia” held in Kaffrine, Senegal on May 19-25, 2013. The roundtable brought together global experts in the area of gender-responsive impact assessment for farmers, to develop a useable monitoring and evaluation (M&E) protocol to guide baseline data collection, identify the locally-specific function, benefits, and beneficiaries of climate services, and measure the added-value of climate services for farmers. This protocol links to and informs the climate service evaluation framework developed during the expert meetings on evaluation of the Climate Services Partnership (CSP) and the World Meteorological Organization Socio-Economic Benefits of Climate Services group.